Respon Ekspor Akibat Shock Nilai Tukar Dan Jumlah Uang Beredar di Indonesia - Miftahul Janah; Wulan Rahmawati; Fariza Novdwikaputri; M. Ghiffari Marshal; Cep Jandi Anwar; Indra Suhendra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The rupiah exchange rate against the US dollar has always fluctuated, due to the instability of economic conditions both at home and abroad. The macroeconomic conditions of the two countries have an influence on the level of exports, especially in Indonesia. The response to export developments that occur in the country is not only influenced by the rupiah exchange rate with the dollar, the money supply (JUB) in Indonesia is also related to the level of exports that occur. If the JUB increases, the number of exports will also increase. So that the relationship between exports, exchange rates, and the money supply has a close relationship with the country's economic conditions. This study aims to analyze how the response in the level of exports in Indonesia is related to the shocks that occur in the exchange rate between the rupiah and the dollar, and also to the money supply in Indonesia through several variable data such as exports, exchange rates, inflation, BI rate, and money. circulating (M2), using data for 2018:M1-2022:M12 using the Vector Error Correction Model (VECM) analysis method. The results show that the response to inflation (INF), the exchange rate (KURS), the money supply (M2), and the bi rate on exports in Indonesia show that the variable response results are positive and the average is stable.